Occupational class and working beyond the retirement age: a cohort study - Virtanen, Marianna; Oksanen, Tuula; Pentti, Jaana; Ervasti, Jenni; Head, Jenny; Stenholm, Sari; Vahtera, Jussi; Kivimäki, Mika (Scandinavian Journal of Work, Environment & Health, 2017)
' ' OBJECTIVES ': 'The aim of this study was to examine occupational class differences in working more than six months beyond the mandatory retirement age and factors that may contribute to these differences. ' ' METHODS ': 'The study comprised a prospective cohort study of a total of 5331 Finnish municipal employees (73% women) who were not on work disability pension and reached the age eligible for old-age pension in 2005–2011. Occupational class included four categories: managers and professionals, lower grade non-manual, skilled manual, and elementary occupations. Survey responses while at work were linked to national health and pension registers. ' ' RESULTS ': 'A total of 921 participants (17.3%) worked beyond the pensionable age. Compared with elementary workers, skilled manual workers had a similar probability [gender-adjusted risk ratio (RR) 0.95, 95% confidence interval (95% CI) 0.72–1.23] while lower grade non-manual workers had a 2.03-fold (95% CI 1.59–2.58), and managers and professionals had a 1.79-fold (95% CI 1.41–2.27) probability of working beyond the pensionable age. Adjustment for physical workload (32.0% in lower non-manual, 36.7% in managers and professionals), work time control (20.4% and 11.4%) and perceived work ability (16.5% and 29.1%) contributed to the largest attenuation for these associations. Analyses using a counterfactual approach suggested greater mediated effects for physical workload and work time control than those observed in traditional mediation analyses. ' ' CONCLUSIONS ': 'Employees with higher occupational classes are two times more likely to continue working beyond the retirement age compared to those with lower occupational classes. A large proportion of these differences were explained by having physically light job, better work time control, and better self-rated work ability among employees with high occupational class.
Keywords: cohort study; counterfactual; health; mediation working condition; occupational class; retirement; socioeconomic